2017
DOI: 10.12678/1089-313x.21.3.87
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Risk Factors and Outcomes of Dance Injury: A Systematic Review

Abstract: Historically, dance medicine and science has focused on the physical aspects rather than the psychological aspects of dance injury. Psychological variables, however, have been shown to influence the occurrence of injury and post-injury outcomes. The purpose of this review was to examine the dance psychology literature and determine the specific psychological factors reported to be associated with the incidence, frequency, and outcome of dance injuries. A systematic literature search was conducted using SPORTDi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 33 publications
2
54
0
1
Order By: Relevance
“…Elite junior performers in sport and performing art are at increased risk for poor functioning and ill-being compared to the average population, due to the unique requirements associated with reaching excellence (Hill A. et al, 2016; Mainwaring and Finney, 2017; Drew et al, 2018). This urges scholars to address risk factors (e.g., traits and conditions) to better safeguard talent development environments (TDEs).…”
Section: Introductionmentioning
confidence: 99%
“…Elite junior performers in sport and performing art are at increased risk for poor functioning and ill-being compared to the average population, due to the unique requirements associated with reaching excellence (Hill A. et al, 2016; Mainwaring and Finney, 2017; Drew et al, 2018). This urges scholars to address risk factors (e.g., traits and conditions) to better safeguard talent development environments (TDEs).…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Pecen et al (2018), professional musicians recognised experiencing psychological challenges related to coping with affective experiences connected with expressive performance and managing personal expectations. Further, research with dancers (Mainwaring and Finney, 2017) and circus artists (Shrier and Hallé, 2011) has highlighted the potential negative effect of intrapersonal demands and their relation to injury.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, future research within dance should investigate other risk factors as well. For instance, several studies have shown that joint range of motion (i.e., lower extremity), dance exposure (i.e., years of training, exposure hours), poor aerobic capacity ( Kenny et al, 2016 ), and stress ( Mainwaring and Finney, 2017 ) are associated with injury risk. These factors might illuminate part of the unexplained variance in the current multivariate regression model and should, therefore, be included in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies aiming at identifying risk factors for ballet and modern dance injuries have shown little consistence due to a lack of quality and level of evidence (Kenny et al, 2016). Moreover, dance medicine and science has traditionally focused on the physical aspects of injuries (Krasnow et al, 1999;Liederbach and Compagno, 2001;Mainwaring and Finney, 2017), while studies including dancers and athletes have shown that psychological constructs might also influence the occurrence of (dance) injuries and affect injury outcomes, including successful rehabilitation, duration of injury, and treatment-seeking behavior (Mainwaring and Finney, 2017;Reardon et al, 2019). Furthermore, mental skills can be considered adaptable (Kenny et al, 2016), which makes them appropriate for preventive measures.…”
Section: Introductionmentioning
confidence: 99%